'Assentados sobre os ombros de gigantes': juventude, ecossistema de empreendedorismo, e entrepreneuring em empresas criadas por jovens - Santos, Éder Danilo Bezerra dos (2019)
This thesis is organized in a three independent chapters format, within the youth entrepreneurship theme, presented as follows. •Chapter 1: The young poor are the biggest victim of violence and unemployment in Brazil. The most recent statists from the document called Atlas da Violência [Violence Atlas] reveal that the social cost of violence in the country amounts to almost 5.9% of its GDP. In addition to the sad cost of lives and lost futures, we are facing a problem of social and economic order far bigger than anywhere else in the world. If chronic violence alone was not enough of a problem, data from IBGE [Brazilian Institute of Geography and Statistics] show that the unemployment caused by the current economic crisis affects 27.3% of the Brazilian youth. That said, this essay discusses the challenges and perspectives from the Brazilian young people, particularly those living in poverty and social vulnerability, and analyses entrepreneurship as emancipation in an alternative view of development, by presenting five propositions on the functions of the university when it comes to the youth and the emancipation perspective. •Chapter 2: The university has a new mission related to promoting entrepreneurship and contributing to the socioeconomic development of its region, and strengthening the local youth entrepreneurship ecosystem. Thus, the aim of this chapter is to understand how the university functions within a local youth entrepreneurship ecosystem. To this end, we conducted a case study in the State of Sergipe, which had its youth entrepreneurship panorama started around 2004, by the initiative of two local universities, and today has other stakeholders and initiatives to promote youth entrepreneurship taking place. The results of this research point to the main components of the local youth entrepreneurship ecosystem, as well as the analysis of the entrepreneurial university functions: (1) educational support; (2) business support; and (3) partnerships support. As a theoretical contribution, this chapter advances on the discussion of the university’s role in a local youth entrepreneurship ecosystem. Practically, it contributes with recommendations aimed at converging the multiple actors in the ecosystem in favor of the youth entrepreneurship. •Chapter 3: Reflecting upon the efficacy of the university as a promoter of entrepreneurship raises some questions. If on one hand there is a consolidated understanding that universities function as bridges between nascent businesses, government, and industry, on the other we still have a limited knowledge on how such institutional support happens in practice. Thus, this chapter begins with an analysis of the theoretical models guiding the university spin-off research, and proposes the entrepreneuring perspective an alternative to study the young entrepreneur as an individual, adopting a case study approach as research method. We identified the main elements of the (trans)formation of the individuals as young entrepreneur, namely: (1) the entrepreneur in the perspective of the practice; (2) the technology in the perspective of the practice; and (1) the university in the perspective of the practice. As a theoretical contribution, the chapter offers new insights into the process of entrepreneuring involving young people. As practical and policy contributions, we critically discuss the actions of the university in such process, and make proposals for a more engaged university.